Rhetoric and reality: A critical review of language policy and legislation governing official minority language use in health and social care in Wales - Prys, Cynog; Hodges, Rhian; Roberts, Gwerfyl Wyn (Linguistic Minorities and Society, 2021)
A concerted attempt is being made by the Welsh Government to revitalize the Welsh language in Wales through language legislation and policy initiatives. This paper explores the political rhetoric and practical reality of these recent legislative developments, as they pertain to the health care sector. It offers a qualitative analysis of written evidence provided by key stakeholders during the consultation process on the new legally-binding requirements of Welsh Language Standards for health care providers in Wales. We argue that these meso-level service providers are critical linchpins within the health care system and that it is at the meso level that full tensions between the macro rhetoric and micro reality occur. This contribution highlights shortcomings and barriers to Welsh language service provision in health care in Wales and recommends the adoption of wide-ranging, holistic approaches to language planning that meet the language needs of patients outlined by the Welsh Government. Keywords: health and social care, language planning, minority language, Welsh, Wales

Social exclusion among official language minority older adults: A rapid review of the literature in Canada, Finland and Wales - Nyqvist, Fredica; Häkkinen, Emilia; Renaud, Alexandre; Bouchard, Louise; Prys, Cynog (Journal of Cross-Cultural Gerontology, 2021)
It has been suggested that older adults from minority linguistic and ethnic communities face higher risks of being socially excluded. The aim of this review was, therefore, to explore and review social exclusion studies conducted among official language minority older adults in three countries, namely Canada, Finland and Wales. A rapid review approach was used to review scientific literature in line with six social exclusion domains. The literature searches were made in Finnish, Swedish, English, French and Welsh and were restricted to research published within the timeline of 2001 – September 2019 and yielded 42 articles. The included studies were categorized into three different domains: socioeconomic influences, social participation and societal conditions. Converging and diverging patterns of social exclusion in old age were identified between the linguistic minorities. Linguistic barriers regarding access to health care and receiving health information were common across the three linguistic contexts, whereas exclusion from social participation was noticed amongst the linguistic minorities in Canada and Wales. Some connections between belonging to a linguistic minority and being exposed to a lower socioeconomic status and higher poverty risk were made, however, these findings were not robust across all three countries. The findings indicated that experiences of exclusion could be considered fairly common among linguistic minority older adults. We conclude that the research evidence presented in the review sheds light on issues of social inequality in old age between linguistic majorities and minorities, thus identifying important aspects of social exclusion to guide future research as well as policy and practice.